Mechanical handling effects on brewers' yeast - Robinson, Andrew (Department of Chemical Engineering, 2025)
Brewery fermentation involves the conversion of sugars to ethanol by yeast with the repeated reuse of the yeast to maximise the overall conversion of sugars to ethanol. Within this environment the yeast is subjected to mechanical handling which exposes the cells to shear stress. It is known that biological particles are sensitive to hydrodynamic stress and the resultant biological response may be observed by a decrease growth rate (Cherry and Papoutsakis, 1988), decreased viability, vitality and fermentation performance (Basson et aI., 1996), release of enzymes (Stathopoulos and Hellums, 1985), the release of fine particles from the cell wall (Lewis and Poerwantaro, 1991) and cell disruption (Engler and Robinson, 1981 ; Zhang et al., 1993). In particular with the handling of yeast, filtration difficulties have been reported as a result of excessive haze production caused by the action of centrifuges (Lim et al., 1992; Siebert et al., 1987). Mannan haze material has also been shown to result from the agitation of yeast slurries in baffled shake flasks (Lewis and Poerwantaro, 1991). The implications of yeast handling in the brewing industry are poor fermentation performance due to decreased yeast viability, foam instabilities caused by the release of protease and the formation of beer haze brought about by abrasion of the cell wall and cell lysis. It is generally accepted brewery practice to minimise the hydrodynamic stress to which the yeast is exposed (Boughton 1983, 1987; Ball, 1994). Few technical reports or rigorous experimental data are however available on the effect of hydrodynamic stress on the yeast in the brewing industry thereby indicating the need for this study. An analysis of the brewing flowsheet highlighted processes that have the potential to cause hydrodynamic stress damage to the yeast. These major processes include the transfer flow of yeast suspensions between the various stages in the yeast propagation plant as well as the pumping and flow of yeast slurries from a fermentation vessel, through a plate and frame heat exchanger to an agitated storage vessel. The separation of low concentrations of excess yeast between primary and secondary fermentations by centrifuges is a further shear environment to which yeast is exposed. Yeast handling occurs between the stages of a 'multiple batch propagation' and at the end of a fermentation when the yeast is in the late exponential growth or stationary phase respectively. The primary objective of this study was to assess the effect of hydrodynamic stress on brewers' yeast quality. Towards this aim, stationary phase yeast was exposed to hydrodynamic shear generated within a laboratory French Press following its aerobic and anaerobic growth. Within the brewery, the centrifugal separation of yeast and flow of yeast slurries through the cropping circuit were investigated with the aim of identifying critical operating conditions to minimise cell damage.